2018
DOI: 10.1051/e3sconf/20183108014
|View full text |Cite
|
Sign up to set email alerts
|

Implementation Of Conservation Policy Through The Protection Of Life Support System In The Karimunjawa National Park

Abstract: The Karimunjawa National Park as the only one marine protected area in Central Java, managed by zonation system has decreased natural resources in the form of decreasing mangrove forest area, coral cover, sea biota population such as clams and sea cucumbers. Conservation has been done by Karimunjawa National Park Authority through protection of life support system activities in order to protect the area from degradation. The objective of the research is to know the implementation of protection and security act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 5 publications
1
2
0
Order By: Relevance
“…For instance, mangrove losses due to conversion into oil palm plantation and other land uses were observed in the islands of Mentawau (West Sumatra), Lankat (North Sumatra), Bawal (West Kalimantan), Seram (Maluku), Bangka Belitung, and Enggano Bengkulu [67]. The results of this study and previous researches (i.e., [59,68]) indicate that mangroves in Indonesia are still threatened by manmade activities despite an increase in management strategies (i.e., [66,69,70]).…”
Section: Threats To Blue Carbon Ecosystemssupporting
confidence: 49%
See 2 more Smart Citations
“…For instance, mangrove losses due to conversion into oil palm plantation and other land uses were observed in the islands of Mentawau (West Sumatra), Lankat (North Sumatra), Bawal (West Kalimantan), Seram (Maluku), Bangka Belitung, and Enggano Bengkulu [67]. The results of this study and previous researches (i.e., [59,68]) indicate that mangroves in Indonesia are still threatened by manmade activities despite an increase in management strategies (i.e., [66,69,70]).…”
Section: Threats To Blue Carbon Ecosystemssupporting
confidence: 49%
“…Conformingly, the results of this study also identified anthropogenic threats (i.e., mangrove cutting, pollution) as the top perceived causes of mangrove degradation. The recognition of human-induced threats to mangroves has been long supported by quantitative researches (i.e., [65,66]) and has been observed not just in Karimunjawa but also in other areas in Indonesia. For instance, mangrove losses due to conversion into oil palm plantation and other land uses were observed in the islands of Mentawau (West Sumatra), Lankat (North Sumatra), Bawal (West Kalimantan), Seram (Maluku), Bangka Belitung, and Enggano Bengkulu [67].…”
Section: Threats To Blue Carbon Ecosystemsmentioning
confidence: 99%
See 1 more Smart Citation